2018
DOI: 10.1158/1538-7445.sabcs17-p6-11-19
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-11-19: Efficacy and patient acceptability of the DigniCaP ScalpCooler to prevent hair loss in breast cancer patients receiving adjuvant chemotherapy

Abstract: Background: Alopecia is a common and distressing adverse effect in breast cancer (BC) patients (pts) receiving adjuvant chemotherapy. The aim of the study was to assess the effectiveness and safety of this device to prevent chemotherapy-induced alopecia in early breast cancer patients (EBCP) receiving adjuvant treatment. The quality of life of pts was also evaluated. Patients and methods: From January to December 2016, a sensor-controlled scalp cooling system (DigniCap:Sysmex Europe GmbH, Norder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…Regarding the positive psychological impact of the DigniCap technology, preventing CIA and improving the quality of life was not signi cantly detected. Vassalli et al (2018) reported no signi cant changes in the quality of life pre-and post-treatment, and even reported an increase in fatigue; by contrast, only anxiety seemed to have decreased in this cohort. Similarly, Pochilo et al ( 2019) reported a decrease in anxiety level with an increase in depressive thoughts.…”
Section: Basic Research 25contrasting
confidence: 53%
See 1 more Smart Citation
“…Regarding the positive psychological impact of the DigniCap technology, preventing CIA and improving the quality of life was not signi cantly detected. Vassalli et al (2018) reported no signi cant changes in the quality of life pre-and post-treatment, and even reported an increase in fatigue; by contrast, only anxiety seemed to have decreased in this cohort. Similarly, Pochilo et al ( 2019) reported a decrease in anxiety level with an increase in depressive thoughts.…”
Section: Basic Research 25contrasting
confidence: 53%
“…Clinical trials (Cigler et al, 2017;Smetanay et al, 2018;Munzone et al, 2019) have been conducted mostly from a multicentric perspective and observational studies. In cohort study designs (Rugo et al, 2012;Fehr et al, 2016;Rugo et al, 2017;Vassalli et al, 2018;Chan et al, 2019;Giarratano et al, 2019;Prochilo et al, 2019;Orlando et al, 2019) prospective observational studies have been conducted mostly in multicentric research, focusing on CIA and quality of life, satisfaction, and patient-reported performance variables in an oncological population diagnosed with breast cancer. All studies reported a good rate of success for the DigniCap technology associated with chemotherapy treatment, particularly, regarding hair loss (average: 25% of CIA).…”
Section: Source Of Articles/studiesmentioning
confidence: 99%